Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 di Kantor Pengadilan Negeri Tondano - Gabriella Mewengkang; Devie S. R. Siwij; Laurens Bulo; Ressy Mewengkang (Tumoutou Social Science Journal, 2026)
This paper aimed to examine how Government Regulation No. 94 of 2021 on  Civil  Servant  Discipline  has  been  put  into  practice  at  the  Tondano District  Court  Class  IB,  focusing  on  attendance  filling  mechanism, punctuality, dispensation, and evaluation. A qualitative descriptive design was employed, gathering evidence through participatory observation, in- depth  interviews,  and  document  review,  analyzed  using  the  interactive model  of  Miles,  Huberman,  and  Saldana. Findings  show  that  the  court operates a digital attendance system through the SIKEP application with facial  recognition  and  location  verification,  though  recurring  server disruptions  remain  a  practical  obstacle.  Most  employees  observe punctuality requirements, while a minority face delays due to commuting distance,  weather,  and  limited  transport.  Dispensation  procedures  run adequately through supervisory communication and the digital platform, and  attendance  evaluation  is  conducted  daily  and  monthly,  resulting  in reprimands and a one-percent salary deduction for latecomers. The study concludes  that  implementation  is  progressing  reasonably  well,  yet sustained effectiveness requires stronger infrastructure investment and a more  developmental rather than purely  punitive approach to employee discipline